The Impact of Worksite Clinics on Teacher Health Care Utilization and Cost, Self-Reported Health Status, and Student Academic Achievement Growth in a Public School District. Issue 8 (August 2018) - Engberg, John B.; Harris-Shapiro, Jon; Hines, David; McCarver, Patti; Liu, Harry H.
Abstract : Objective: The aim of this study was to examine the impact of worksite clinics on health care utilization and cost, self-reported health status, and student achievement growth in a public school district. Methods: We used insurance claims, health risk assessment, and student achievement growth data for active teachers during 2007 to 2015. A difference-in-differences approach was applied to measure the impact of worksite clinics. Results: Compared with using a community-based clinic as the usual source of primary care, using a worksite clinic was associated with significantly lower inpatient admissions (53 vs 31 per 1000 teacher years), annual health care cost ($5043 vs $4298 in 2016 US dollars, a difference of $62 per teacher per month), and annual absent work hours (63 vs 61). No significant differences were detected in self-reported health status or student achievement growth. Conclusion: Worksite clinics reduce teacher health care cost and absenteeism. Abstract : Supplemental Digital Content is available in the text